(untitled) (Research, Society and Development, 2022)
The present study aims to reflect on the academic itinerary of the undergraduate nursing student. This is a reflective theoretical essay built from the authors’ critical thinking and experiences, theoretically supported by scientific publications. Among the various reasons that lead young people to choose the nursing profession, interest and aptitudes, the need for professional advancement in the field of nursing, family influence and, finally, the failure to access courses in other areas of care stand out. health. Different course proposals stand out in the national scenario, with different variations in workloads, type of offer, curricular structures and offer of very diversified subjects and experiences, and educational proposals that reflect innovative curricula that overcome hegemonic practices are rare. This study was guided by reflections on situations that undergraduate students may face as daily academic demands, in order to provide knowledge and support educational institutions in the proposition and implementation of undergraduate nursing courses and student support actions.